Efficacy of Isotretinoin in The Management of Enlarged Facial Pores in Moderate and Severe Acne Vulgaris Patients - Waleed Gaber; Abd Al Shakour Abd Al Wahed; Mohamed Kamel (International Journal of Medical Arts, 2023)
Background: A multitude of treatment options have been used in dealing with enlarged facial pores. However, there is a lack of studies assessing the effectiveness of oral isotretinoin, which is commonly used to treat acne, as a treatment option for enlarged facial pores in such patients.Aim of the work: To assess the effectiveness of oral isotretinoin in reducing the size of enlarged facial pores in patients with moderate and severe acne vulgaris.Patients and Methods: Forty cases with moderate and severe acne vulgaris, characterized by the presence of multiple to numerous inflammatory papules, pustules, nodules, and scarring, as well as enlarged facial pores, were prescribed oral isotretinoin. The daily dosage ranged from 0.5 to 1.0 mg/kg/day, with a total cumulative dose of 120 mg/kg administered over a 6-month treatment period. For each patient, dermoscopic photos were taken of the enlarged facial pores located on the tip of the nose, where sebum production is high and the pores are clinically visible. These photos were captured both before and after the 6 months of treatment. The total surface area of all facial pores was measured using Fiji software, and a comparison was made between the measurements before and after treatment to determine any differences.Results: All of the treated patients exhibited a statistically significant decrease in the size of their facial pores after treatment [0.46 ± 0.2 mm2], as compared to the size of their facial pores before treatment [0.67 ± 0.3 mm2], with a p-value < 0.05.Conclusion: In our study, Isotretinoin has been demonstrated to be a safe and effective treatment modality for managing enlarged facial pores in patients with moderate and severe acne vulgaris.